2019
DOI: 10.1016/j.envres.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes during pregnancy in gut microbiota and methylmercury biomarkers, and reversal of microbe-exposure correlations

Abstract: Objective: Gut microorganisms contribute to the metabolism of environmental toxicants, including methylmercury (MeHg). Our main objective was to investigate whether associations between biomarkers for prenatal MeHg exposure and maternal gut microbiota differed between early and late gestation.Methods: Maternal blood and stool samples were collected during early (8.3-17 weeks, n=28) and late (27-36 weeks, n=24) gestation. Total mercury and MeHg concentrations were quantified in biomarkers, and inorganic mercury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
3
19
3
Order By: Relevance
“…Several previous reports showed that the microbiota composition changes during pregnancy. In the present study, unlike that in a previous study, Proteobacteria and Actinobacteria did not change during pregnancy, but the proportion of the TM7 phylum did change.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Several previous reports showed that the microbiota composition changes during pregnancy. In the present study, unlike that in a previous study, Proteobacteria and Actinobacteria did not change during pregnancy, but the proportion of the TM7 phylum did change.…”
Section: Discussioncontrasting
confidence: 92%
“…In the present study, unlike that in a previous study, Proteobacteria and Actinobacteria did not change during pregnancy, but the proportion of the TM7 phylum did change. Previous studies reported that the gut microbiota in different populations are distinct from one another, and that long‐term dietary habits affect human gut microbiota. The differences between previous studies and the present study might be due to different ethnicities and dietary habits of the study populations.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The mechanisms involved in the complex bio-physicochemical process of Hg methylation and demethylation remain to be fully understood. However, MeHg metabolism is the core research in experiments focused on methylation/demethylation processes in GM, that is considered to be involved in the biochemical interplay responsible for its demethylation to inorganic mercury (64).…”
Section: Mercurymentioning
confidence: 99%
“…However, this pro-inflammatory status is also implicated in metabolic alterations during pregnancy, which contribute to ensuring a healthy pregnancy. The microbial changes in the gut mainly manifest as an increase in Actinobacteria and Proteobacteria phylum, alongside a reduction in microbial diversity and butyrate-producing bacteria [32]. Some studies have identified shifts in the gut microbiota during pregnancy [33,34], while others have failed to identify any microbial changes during gestation [35].…”
Section: Maternal Adaptation During Pregnancy: Impact On the Microbiotamentioning
confidence: 99%